Enhanced catalytic activity of α-Fe2O3 with the adsorption of gases for ammonia synthesis - Qureshi, S. (Trans Tech Publications Ltd, 2017)
Ab initio density functional theory employed to study the adsorption of hydrogen and nitrogen gas molecule on the α-Fe2O3 (111) surface for ammonia synthesis. The calculated adsorption energy is-4.70kcal/mol,-4.60kcal/mol,-4.38kcal/mol and-3.77kcal/mol for different orientations of adsorbed gas molecules and shows that system is stable and gas molecules have adsorbed. It can also be seen with adsorption of gas molecules the net spin of hematite enhanced from 0 to 2 hence confirms the activity of hematite surface. Hematite nanowires synthesized by oxidation method. Raman spectrum analyses demonstrates that the nanowires are single-crystalline. Field Emission Scanning Electron Microscopy (FESEM) reveals that the nanowires have lengths of 10-25 μm. The magnetic saturation of the nanowires is 15.6 emu/g investigated by vibrating sample magnetometer (VSM). Ammonia was synthesized by magnetic induction method using the hematite nanowires as catlyst and quantified by Kjeldahl method. It is found that the role of gases adsorption was able to enhance catalytic activity of hematite nanowires for the ammonia synthesis. This green synthesis method could be a contender to the Haber-Bosch process currently used by the industry. © 2017 Trans Tech Publications, Switzerland.